Malus Hosts–Erwinia amylovora Interactions: Strain Pathogenicity and Resistance Mechanisms - Emeriewen, Ofere Francis; Wöhner, Thomas; Flachowsky, Henryk; Peil, Andreas (Frontiers in Plant Science, 2019)
The bacterium, Erwinia amylovora, deposits effector proteins such as AvrRpt2EA in to hosts through the type III secretion pathogenicity island to cause fire blight in susceptible Malus genotypes. A single nucleotide polymorphism in the AvrRpt2EA effector plays a key role in pathogen virulence on Malus hosts by exchanging one cysteine to serine in the effector protein sequence. Fire blight resistance quantitative trait loci (QTLs) were detected in a few apple cultivars and wild Malus genotypes with the resistance of wild apples generally found to be stronger than their domestic relatives. The only candidate and functionally analysed fire blight resistance genes proposed are from wild apple genotypes. Nevertheless, the aforementioned AvrRpt2EA SNP and a couple of effector mutants of E. amylovora are responsible for the breakdown of resistance from a few Malus donors including detected QTLs and underlying R-genes. This review summarises a key finding related to the molecular basis underpinning an aspect of virulence of E. amylovora on Malus genotypes, as well as mechanisms of host recognition and specificity, and their implications on the results of genetic mapping and phenotypic studies within the last five to six years. Although the knowledge gained has improved our understanding of the Malus – E. amylovora system, more research is required to fully grasp the resistance mechanisms in this genus especially as they pertain to direct interactions with pathogen effectors.